IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING (SAW) PEMILIHAN KUALITAS DEPOT AIR MINUM - Roy Nuary Singarimbun (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
Water is one of the important components of life. Many things depend on water, especially for daily needs. Water quality in general indicates the quality or condition of water associated with a particular activity or need. Meanwhile, quantity refers to the amount of water needed by humans in certain activities. However, in general, there is not much attention to the quality and standardization of the safety of refilled drinking water that is consumed and produced by the water depot. The proliferation of drinking water refill businesses led to the idea of researching which depots have good water quality and health. So a decision support system is needed that can analyze the water quality assessment criteria at the depots. By using the Simple Additive Weighted (SAW) method, it can be applied in selecting the quality of water depot based on the website. The data will be stored using the Mysql application.